The Rural-Urban Interface
IX, 203 p. 62 illus., 39 illus. in color.
Keywords: Bengaluru is one of the fastest growing megacities in India. As such, it provides an in-situ laboratory for studying rural-urban transitions. While urbanization is most evident in the changing landscape with increasing built-up areas, it comes along with changes in ecosystem functions, new economic opportunities, changes in social organization and individual attitudes and behavior. All of these processes are interlinked and mutually depend on each other. This book attempts to integrate studies from a wide scope of disciplinary perspectives and at different spatial scales under the framework of complex social-ecological systems. Agriculture is the prime example of a system in which humans interact with their biophysical environment, and the production systems in the rural-urban interface are profoundly affected by urbanisation. Intensification and diversification of agriculture are immediate responses to urban pressures and demands,and are linked as much to resource (over-)use as to commercialisation. Yet, little is known about the spatial patterns of agricultural transformation in areas of urban sprawl. The focus of the contributions here is explicitly on the interface, in-between the rural and urban systems. It thus differs from the urban-centered perspective of city planners as well as from the rural predominance in most of the agricultural research. In the present volume this focus is implemented by analysing samples along a spatial gradient representing different stages of urbanization. Ongoing time series analyses and a panel study will complement the spatial approach by a temporal dimension.